2003
DOI: 10.1099/jmm.0.04991-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of terminal RFLP analysis to characterize oral bacterial flora in saliva of healthy subjects and patients with periodontitis

Abstract: Terminal restriction fragment-length polymorphism (T-RFLP) analysis was applied to characterize oral bacterial flora in saliva from 18 healthy subjects and 18 patients with periodontitis. The 16S rRNA genes (rDNAs) of oral bacteria and spirochaetes in saliva were amplified by PCR with a 69carboxy-fluorescein (6-FAM)-labelled universal forward primer (27F) and a universal reverse primer (1492R) or the Spirochaeta-selective reverse primer. The 16S rDNAs were digested with restriction enzymes with 4 bp recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
106
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 40 publications
2
106
0
1
Order By: Relevance
“…The present results indicated that the TRFLP patterns derived from patients with periodontitis were significantly different from the patterns of periodontally healthy subjects. The data confirm findings from previous studies, which reported that the saliva from patients with periodontitis contains a special bacterial diversity (9,19). Notably, the present TRFLP results also suggested that the age of the subjects had a significant effect on the oral bacterial flora.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The present results indicated that the TRFLP patterns derived from patients with periodontitis were significantly different from the patterns of periodontally healthy subjects. The data confirm findings from previous studies, which reported that the saliva from patients with periodontitis contains a special bacterial diversity (9,19). Notably, the present TRFLP results also suggested that the age of the subjects had a significant effect on the oral bacterial flora.…”
Section: Discussionsupporting
confidence: 82%
“…The TRFLP patterns allow the rapid comparison of the community composition among patients with periodontitis, and can show host-specific relatively stable oral bacterial flora (9). The present results indicated that the TRFLP patterns derived from patients with periodontitis were significantly different from the patterns of periodontally healthy subjects.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…When the target of PCR is 16S ribosomal DNA, the terminal restriction fragments pattern reflects the taxonomic diversity of the bacteria in the sample. T-RFLP is a rapid and efficient approach for successfully obtaining profiles of the various members of a complex microbial community, for example, human feces (10,25), chicken cecal samples (6), pig colon (19), rat feces (15), oral bacterial flora (24), soil (20,21), and marine sediments (28). The present study is the first to our knowledge to analyze 40 fecal samples using T-RFLP and to compare them using a dendrogram.…”
mentioning
confidence: 99%